The INFLUENCE OF BUSINESS MANAGEMENT AND MENTORING ON THE BUSINESS PERFORMANCE OF UMKM ACTORS IN KARAWANG DISTRICT - Rahayu, Budi; Suyaman, Dede Jajang; Nurhasanah, Nunung; Nadeak, Banuara (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The importance of increasing Human Resources, especially for MSME players, will be able to increase knowledge which will have an impact on improving business performance. What the Karawang Regency Cooperatives and SMEs Service has done in this effort is to increase competence in terms of business management and mentoring. This research aims to determine the partial and simultaneous influence of business management and mentoring on improving Karawang Regency MSME business. The type of research is quantitative with descriptive verification analysis. The data analysis method used is multiple linear regression analysis. The number of samples used was 399 people. The sampling technique used in this research was a simple random sampling technique. The research results show that both partially and simultaneously show that business management and mentoring have an influence on the business performance of MSMEs in Karawang Regency. This means that increasing knowledge of business management and providing assistance has an impact on increasing the business performance of MSMEs in Karawang Regency. Key words: business management, mentoring, business performance